2011
DOI: 10.1016/j.jmoldx.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Improved Sample Preparation for Rapid, Direct Identification from Positive Blood Cultures Using Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) Mass Spectrometry

Abstract: Matrix-assisted laser desorption ionization time-offlight mass spectrometry (MALDI-TOF MS) is widely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
133
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 22 publications
(28 reference statements)
6
133
0
3
Order By: Relevance
“…Other rapid methods for detection of pathogens in positive blood cultures such as MALDI-TOF analysis perform better with Gram-negative than Gram-positive isolates; they show significant variability in performance, with percentages of isolates accurately detected and identified ranging from 37% to 86.3% depending on the protocol (16)(17)(18). Similar issues have been associated with DNA probe-based assays that target multiple pathogens, with discordant results ranging from 11% to 21% for Gram-positive cocci (22,23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other rapid methods for detection of pathogens in positive blood cultures such as MALDI-TOF analysis perform better with Gram-negative than Gram-positive isolates; they show significant variability in performance, with percentages of isolates accurately detected and identified ranging from 37% to 86.3% depending on the protocol (16)(17)(18). Similar issues have been associated with DNA probe-based assays that target multiple pathogens, with discordant results ranging from 11% to 21% for Gram-positive cocci (22,23).…”
Section: Discussionmentioning
confidence: 92%
“…Other approaches included molecular amplification methods coupled with probebased detection (10,13,14). Matrix-associated laser desorption ionization-time of flight (MALDI-TOF) analysis for identification of bacterial isolates from positive blood cultures is another recent development (15)(16)(17)(18). Each methodology has limitations, for example, the inability to detect resistance markers (PNA-FISH and MALDI-TOF) or problems with detecting polymicrobial infections (MALDI-TOF) (16,17).…”
mentioning
confidence: 99%
“…Especially, for positive blood cultures it is very important to quickly identify the microorganisms and to get information about possible resistances. MALDI-TOF MS provides quick identification (12,(15)(16)(17), and the MALDI-TOF MS-based resistance assay facilitates the rapid detection of ␤-lactamase-mediated resistance. Using the respective antibiotics/inhibitor combinations, differentiation and confirmation of the underlying ␤-lactamase also are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Details on MALDI-TOF MS have been provided by Schubert et al, 29 where pathogens were identified from an agar plate. Recently, however, Sepsityper (Bruker, Billerica, MA, USA), a preparation method prior to MALDI-TOF MS, has been developed, allowing MALDI-TOF MS to be used directly on a positive blood culture bottles without the need for growing pathogens on an agar plate.…”
mentioning
confidence: 99%